The international rule of law : rise or decline? - Krieger, Heike; Nolte, Georg, 1959-; Zimmermann, Andreas (Oxford : Oxford University Press, 2019)
This volume examines the role of international law in a changing global order, asking if, under the current significantly changing conditions, we can still observe an increasing juridification of international relations based on a universal understanding of values.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2019).
Keywords: Rule of law; International law